Efeitos territoriais do Programa Nacional de Alimentação Escolar (PNAE) e Programa de Aquisição de Alimentos (PAA) para o fortalecimento da agricultura familiar nos municípios de Dracena/SP e Verê /PR - Silva, Tiago Martins da (2024)
The main objective of the research was to investigate the territorial effects of the National School Feeding Program (PNAE) and the Food Acquisition Program (PAA) to strengthen family farming in the municipalities of Dracena/São Paulo and Verê/Paraná, based on their implementation in the aforementioned municipalities, from 2006, until 2021. The methodological procedures used were bibliographic review, documentary research, data collection from secondary and primary sources. It was found that the territorial effects of PNAE and PAA policies in the municipalities of Dracena and Verê can guide sustainable rural development, contributing to the improvement of the socioeconomic conditions of rural producers, farmer associations and family cooperatives. However, fluctuations were identified in the participation of these collective organizations in these institutional programs in the period analyzed, mainly due to the institutional changes in these programs, especially in the PAA, in which the federal government's budget cuts from 2013 onwards have impacted negatively affect access to the benefits of this policy that facilitates the commercialization of family food production. The development of the programs, for the sake of comparison in the two municipalities, depended on local particularities, especially on the strategies adopted by family farmers through their political and territorial organizations. In that location where family mobilization and organization is consolidated, such as in Dracena, the confrontation was stronger, also creating other marketing strategies through short circuits. In that location where the political organization is more fragile, the difficulties have not yet been overcome satisfactorily, as in the case of Verê.